Strengthening Religious Moderation Values Based on School Culture - Yuniar, Yuniar; Wigati, Indah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to explore forms of school cultural activities which are allegedly an effort to strengthen students' religious moderation values. Schools are considered as institutions that are capable of coloring and even changing the mindset, character and even behavior of its citizens so that from the womb of the school it is hoped that human beings will be born who reconcile, spread love and create national unity and integrity. This study uses a qualitative research method with a phenomenological approach, namely uncovering phenomena or symptoms that occur related to strengthening religious moderation values through school culture. In this study, the research subjects were selected purposively, so the informants in this study were the head of SMA Y Palembang, the representatives, the teacher council, students, stakeholders and other relevant informants where data was collected by observing a number of objects related to research problems. and in-depth interviews with a number of informants and supported by data collected using documentation techniques. The data analysis technique used in this study is qualitative data analysis with three activities namely data reduction, display and verification.The results of the study show that the school culture developed at SMA Y is classified into two cultural groups, namely formal activities which include morning breafing activities, and collective prayer, core activities by applying methods oriented towards strengthening the value of moderation and closing activities which contain motivation and advice. In these activities, the values of religious moderation are strengthened, including the value of tolerance or tasamuh through morning briefings and joint prayers with school members and in class activities through the discussion method of strengthening values not only on tasamuh values but on the values of tatawur walibtikar or dynamic and innovative while in closing activitiesÂ in the form of motivation and advice by strengthening the value of tasamuh andÂ tawazun as well as tawasuth fellow school members. Furthermore, in the form of non-formal activities there are spiritual activities and candles where these two activities are religious study activities for Muslims and non-Muslims which in their implementation link tasamuh values. In addition, there are also field trips and social services that seek to strengthen the values of tawasuth, tasamuh and tawazun among school members. It turns out that schools with relatively diverse students through school culture are able to strengthen the values of religious moderation in order to create peace and harmony among school members.